2018
DOI: 10.1155/2018/7063137
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Factitious Hyperglycemia in a Patient on Intravenous Ascorbic Acid

Abstract: Finger stick blood glucose meters are widely used in outpatient and inpatient settings. However, various factors can affect accuracy of readings from these meters. Here we present a patient who had spurious glucose elevation on these meters while being on intravenous ascorbic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
6
1
Order By: Relevance
“…In the study by Juan He et al, surprisingly significantly lower value was obtained for POC glucose as compared to LG values before hdVC infusion (158.08 ± 62.08 mg/dl vs 186.25 ± 71.50 mg/dl, P<0.001) or after hdVC treatment (142.90 ± 58.91 mg/dl vs 186.74 ± 72.74 mg/dl, P<0.001.This result is different from spurious higher values of POC glucose reported in the studies and case reports published so far (10,11,12). Juan He et al opine that the colorimetric method used in their study principally differs in mechanism from studies that used glucose dehydrogenase pyrroloquinoline quinine for POC glucose measurement (1).…”
Section: Accepted Manuscriptcontrasting
confidence: 72%
See 1 more Smart Citation
“…In the study by Juan He et al, surprisingly significantly lower value was obtained for POC glucose as compared to LG values before hdVC infusion (158.08 ± 62.08 mg/dl vs 186.25 ± 71.50 mg/dl, P<0.001) or after hdVC treatment (142.90 ± 58.91 mg/dl vs 186.74 ± 72.74 mg/dl, P<0.001.This result is different from spurious higher values of POC glucose reported in the studies and case reports published so far (10,11,12). Juan He et al opine that the colorimetric method used in their study principally differs in mechanism from studies that used glucose dehydrogenase pyrroloquinoline quinine for POC glucose measurement (1).…”
Section: Accepted Manuscriptcontrasting
confidence: 72%
“…Glucose and vitamin C have similar molecular structures with both bearing 6-carbon molecules. Oxidation of ascorbic acid by glucose oxidase and dehydrogenase generates electric current measured as glucose (11). Falsely elevated POC glucose can trigger an inappropriately aggressive treatment response leading to patient morbidity and mortality (10).…”
mentioning
confidence: 99%
“…Based on similar studies, it was because of the role of reguler exercise to regulate BG level as its energy source for exercise and the improvement of muscle GLUT4 (glucose transpoter-4) expression that lead to an uptake more of blood glucose by cells [13]. Vasudevan and Hirsch [14] and Sharma et al [15] also found the BG elevation due to intravenous ascorbic acid. Yet, the other study by Dakhale et al [16] stated that ascorbic acid consumption reduced the BG level in diabetic patients.…”
Section: Bgmentioning
confidence: 99%
“…Amongst other factors, high concentration of ascorbic acid interfere with glucose readings from finger stick blood glucose (FSBG) meters [36]. A classic case of marked interference with FSBG readings is due to intravenous ascorbic acid, because the devices recognized ascorbic acid as glucose and erroneously detects hyperglycemia if ascorbic acid levels are high.…”
Section: (C) Incorrect Glucose Readingsmentioning
confidence: 99%